How do you solve #2(x-2)^(2/3) = 50#?
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the equation 2(x-2)^(2/3) = 50, you can follow these steps:
- Divide both sides of the equation by 2: (x-2)^(2/3) = 25.
- Cube both sides of the equation to eliminate the fractional exponent: [(x-2)^(2/3)]^3 = 25^3.
- Simplify the left side of the equation: (x-2)^2 = 25^3.
- Take the square root of both sides to remove the exponent: √[(x-2)^2] = √(25^3).
- Simplify the equation: x-2 = 25√25.
- Evaluate the square root of 25: x-2 = 25 * 5.
- Simplify the equation: x-2 = 125.
- Add 2 to both sides of the equation: x = 125 + 2.
- Solve the equation: x = 127.
Therefore, the solution to the equation 2(x-2)^(2/3) = 50 is x = 127.
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7